WORK REORGANISATION AND DECENT WORK IN THE FOOD AND BEVERAGE INDUSTRY IN LAGOS STATE, NIGERIA (2017)
Decent Work (DW) is productive work in which workers’ rights, adequate income and social protection are guaranteed. However, competition and diversity in labour market affects DW. Previous studies concentrated on decent work deficits, but few focused on the effects of work reorganisation on DW. This study, therefore, investigated the influence of work reorganisation on decent work in the Food and Beverage industry in Lagos State, Nigeria. Neo-liberal and Social Action theories provided the framework. Research design was cross-sectional survey. Multi-stage sampling procedure was employed to select the respondents. Four organisations were purposively selected: Nigerian Bottling Company and Cadbury Nigeria Plc, (Food sub-sector) Guinness Plc and Nigerian Breweries Plc (Beverage sub-sector). The organisations were selected based on their business duration and reorganisations that had affected workers over the past three decades. A total of 856 permanent and non-permanent workers were proportionately selected as follows: Food sub-sector (555) and beverage sub-sector (301). A semi-structured questionnaire was used to elicit information on socio-economic characteristics, indices that constituted DW, perception about effects of work reorganisation on workers’ benefits, treatment of permanent and non-permanent workers and effects of work reorganisation on workers’ access to terminal benefits. A total of 24 In-depth interviews were conducted among management (4), senior (4), junior staff (4), non-permanent workers (4) and eight Trade unions leaders across the sub-sectors. Quantitative data were analysed using descriptive and multivariate statistics (P<0.05), while qualitative data were content analysed. Respondents’ age was 33.3±4.6years, 73. 7% were males, 59.8% were married and 37.6% had first degree/HND. Indices of DW in both industry indicated protection of workers (95.8%), participation in union activities (79.6%), medical health care for permanent workers’ dependents (49.7%) opportunity in employment (91.6%) and productive work processes (86.8%). Reorganisation in both sub-sectors led to casualisation in Nigerian Bottling Company (60.6%) and 51.6% in Guinness, outsourcing in Cadbury (24.6%) and downsizing in Nigerian Breweries (28.3%). Work reorganisation has led to improvement in workers’ bonuses (55.8%), allowances (66.6%) and health insurance (47.8%) in the Beverage than the food Industry. Casualisation and outsourcing did not encourage decent treatment of non-permanent workers (54.7%) compared to the permanent staff (85.8%) in both sub-sectors. Casualisation affected workers’ right to pension and gratuity benefits of non-permanent workers (65.2%) than permanent workers (31.7%) in both sub-sectors. Casualisation had significantly affected decent work in the food industry (r2=0.0409) than the beverage industry (r2=0.448). There was significant relationship between work reorganisation(r2=0.043) and decent work treatment of non-permanent staff (r2= 0.084).Work reorganisation led to outsourcing, casualisation, downsizing and repositioning in both sub-sectors and it also weakened the collective bargaining power of trade unions within the industry. Work reorganisations such as outsourcing, casualisation and downsizing negatively affected Decent Work in the Nigerian Food and Beverage industry. Therefore, stakeholders should put effective monitoring mechanisms in place to enhance decent work in food and beverage industry